MODEL OF TEAMWORK-BASED IMPROVEMENT OF TEAM PERFORMANCE AT REgIONAL SECRETARIAT OF SEMARANG REGENCY - Endang Pudjiati; Mutamimah Mutamimah (IJIBE (International Journal of Islamic Business Ethics), 2017)
This study aims to examine the effect of communication and trust in teamwork and its impact on team performance. The research problem is how to improve team performance through communication and trust by mediated teamwork. The sample of this study is the employees of the Regional Secretariat of Ungaran as much as 115 respondents. Regression analysis done with Statistical Package of Social Science (SPSS) software, was used to analyze data. The analysis showed that communication and trust significantly influenced teamwork in improving team performance. The empirical findings indicated that communication significantly affected teamwork; trust had a significant effect on team performance; communication had significant influence on teamwork; trust had a significant effect on team performance; and teamwork had a significant effect on team performance .Keywords: communication, trust, teamwork and team performance